MODEL FLIPPED CLASSROOM BERBANTUAN GOOGLE CLASSROOM TERHADAP HASIL BELAJAR MATEMATIKA - Dilla, Nurfadilla (Journal of Mathematics Learning Innovation, 2022)
This study aims to determine the effect of using the modelflipped classroom assisted by google classroom on learning outcomesmathematics. This type of research used is quantitative researchwith a Real Experiment approach (True experiment design)involving two treatment groups. SampleThis research was all students of class VII SMP Negeri 2Patampanua. The data collection techniques in this study namelyby using observation and tests (pre-test and post-test) todistinguish student learning outcomes. For Data Analysisusing descriptive analysis and inferential analysis. Research resultshows that: The effect of using the flipped classroom modelassisted google classroom is better than modeldirect learning of mathematics learning outcomes in SMP Negeri 2Patampanua. The results of student learning tests taught by modelsflipped classroom assisted learning google classroom hasa significant difference compared to the results of student learning teststaught by using the direct learning model so thatit can be said that the use of the Flipped Classroom model is helpfulgoogle classroom affects student learning outcomes